Outcome of Patients Admitted with Exertional Heat Related Illness in Intensive Care Unit of Tertiary Care Hospital - Amatya, Bishwo Ram; Shrestha, Bikal; Rayamajhi, Mallika; K.C., Nagendra Bahadur; Karki, Pranaya (Birat Journal of Health Sciences, 2019)
Introduction: Exertional heat related illness particularly heat stroke is very common life threatening condition that frequently occur in young military trainee due to high ambient temperature and humidity. Objective: The study was undertaken to identify its outcome in recruits admitted in intensive care units of military tertiary care hospital. Methods: An observational cross-sectional descriptive study was done among those recruits admitted in Intensive Care Unit of military tertiary care hospital with diagnosis of heat related illness from June 2016 to August 2017 A.D. Data based on hospital case records were collected and analyzed using SPSS version 22. Primary outcome studied was mortality. Secondary outcomes studied were length of stay in ICU, hospital and on ventilator. Results: Out of 17 recruits, 12 were diagnosed as heat exhaustion and 5 were diagnosed as heat stroke. SOFA score for heat stroke and heat exhaustion patients ranged from 2-16 and 0- 2 with respective mortality rate 7-95% and 0-7%. APACHE II score for heat stroke and heat exhaustion patients ranged from 5-33 and 0-5 with respective mortality rate 5.80-73% and 0-5.80%. There was no mortality among 12 heat exhaustion patients. Out of 5 heat stroke patients, 3 died with 60% mortality rate. Heat stroke patients had maximum stay of 4 days in ICU, hospital for 5 days and ventilator for 4 days. Conclusion: Exertional heat related illness is common in young military trainee with heat exhaustion and heat stroke being common causes for ICU admission. Heat stroke has higher mortality rate due to multiple organ dysfunction.